2006
DOI: 10.1097/fbp.0b013e3280116e6f
|View full text |Cite
|
Sign up to set email alerts
|

Maternal deprivation specifically enhances vulnerability to opiate dependence

Abstract: Maternal deprivation has been shown to increase vulnerability to morphine dependence and to disturb the enkephalinergic system in adulthood. To study whether or not this vulnerability to opiates is a specific feature, we examined oral self-administration behaviour of various reinforcing substances. Experiments were performed with morphine (25 mg/l), ethanol (10%), amphetamine (25 mg/l) and cocaine (100 mg/l). Drugs were available in a continuous free choice paradigm during 3 months. Cocaine and ethanol consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…This indicates that dronabinol treatment did not affect the ability to sense the aversive taste of morphine. There is not always a concordance in the ability of opioids to produce CPP and engender self-administration in rats (for review, see Bardo and Bevins, 2000;Vazquez et al, 2006). Context-drug associative learning (CPP) is likely fundamentally distinct from the acquisition of a drug-reward or -reinforced response at least in part because they are subserved by distinct neuropharmacological circuitry (for review, see Bardo and Bevins, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that dronabinol treatment did not affect the ability to sense the aversive taste of morphine. There is not always a concordance in the ability of opioids to produce CPP and engender self-administration in rats (for review, see Bardo and Bevins, 2000;Vazquez et al, 2006). Context-drug associative learning (CPP) is likely fundamentally distinct from the acquisition of a drug-reward or -reinforced response at least in part because they are subserved by distinct neuropharmacological circuitry (for review, see Bardo and Bevins, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of morphine solution consumption was performed during 12 weeks using a two-bottle choice paradigm as described (Vazquez et al, 2005(Vazquez et al, , 2006. The rats were first trained to consume water for 5 days to habituate the rats to the free choice.…”
Section: Morphine Oral Self-administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…cannabinoid receptor agonist CP-55940 either post-natally (Singh et al, 2006) or during adolescence (Biscaia et al, 2008). We reported that exposing neonatal male rats to an episode of 3 h per day of maternal deprivation (deprivation of new born pups from their mothers as well as littermates from each other) from postnatal days 1e14 induces long-term behavioral and biochemical alterations that resemble opiate dependence, with an escalation behavior in morphine consumption test and an increase of weight gain after morphine removal (Vazquez et al, 2005a(Vazquez et al, , 2006. Interestingly, adolescent exposure to chronic THC blocks morphine dependence in maternally deprived (D) rats (Morel et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…In males, maternal separation increases intake of oral amphetamine (Vazquez et al (2006) and i.v. cocaine (Kosten et al, 2000(Kosten et al, , 2004Zhang et al, 2005;Moffett et al, 2006), although one study using a 24-h discrete trial reinforcement schedule found no effect of maternal separation in cocaine self-administration in either male or female rats (Lynch et al, 2005).…”
Section: B Social Influencesmentioning
confidence: 99%